The Measurement and Preliminary Application of the Concept of Family Centrality - Wan, Xinran; Wang, Wei; Wang, Shengnan; Shan, Geyan; Li, Yongxin (Frontiers in Psychology, 2022)
Family centrality refers to value judgment regarding the relative importance of family in an individual’s life. In contrast to bidirectional research in the field of work-family relationship, much work had done about the work centrality, whereas few researches discussed family centrality as an independent concept. Thus, the present study systematically discussed the concept of family centrality in Chinese culture and the preliminary validation of its measurement through two studies. Results of Study 1 supported that the Family Centrality Questionnaire (FCQ) has a single-factor structure with good reliability and validity. Additionally, family centrality and work centrality are two independent concepts that can be distinguished on conceptional and applicational levels. Results of Study 2 showed that family centrality had an indirect effect on life well-being through life involvement (β = .073, 95% CI [.032, 0128]), and work centrality had an indirect effect on work well-being through work involvement (β = .089, 95% CI [.046, .142]). Further, family centrality had a spillover effect on work well-being through work involvement (β = -.079, 95% CI [-.125, -.42]), and work centrality has a spillover effect on life well-being through family involvement (β = -.053, 95% CI [-.095, -.22]). Overall, the results showed that the FCQ can be used as a scientific measurement for future research.